Bacterial Culture of Neonatal Sepsis - AH Movahedian; R Moniri; Z Mosayebi (Tehran University of Medical Sciences, 2006)
Neonatal bacterial sepsis is one of the major cause of morbidity and mortality in neonates. This retrospective study was performed to determine the incidence of bacterial sepsis with focus on Gram negative organisms in neonates admitted at Beheshti Hospital in Kashan, during a 3-yr period, from September 2002 to September 2005. Blood culture was performed on all neonates with risk factors or signs of suggestive sepsis. Blood samples were cultured using brain heart infusion (BHI) broth according to standard method. From the 1680 neonates 36% had positive blood culture for Pseudomans aeruginosa, 20.7% for Coagulase negative Staphylococci, and 17% for Klebsiella spp. Gram-negative organisms accounted for 72.1% of all positive cultures. The overall mortality rate was 19.8% (22 /111) of whom 63.6% (14 /22) were preterm. Pseudomona aeruginosa and Klebsiella spp. showed a high degree of resistance to commonly used antibiotics (ampicillin, gentamicin) as well as third generation cephalosporins. Continued local surveillance studies are urged to monitor emerging antimicrobial resistance and to guide interventions to minimize its occurrence.